Submerged landscapes, marine transgression and underwater shell middens: Comparative analysis of site formation and taphonomy in Europe and North America. (15th April 2021) - Hale, Jessica Cook; Benjamin, Jonathan; Woo, Katherine; Astrup, Peter Moe; McCarthy, John; Hale, Nathan; Stankiewicz, Francis; Wiseman, Chelsea; Skriver, Claus; Garrison, Ervan; Ulm, Sean; Bailey, Geoff
Abstract: Shell middens, sometimes in the form of mounds of great size, are a ubiquitous indicator of coastal settlement and exploitation of marine resources across the world. However, shell middens are relatively rare before the mid-Holocene because most palaeoshorelines before that time are now submerged by sea-level rise since the Last Glacial Maximum (LGM). Previously reported examples of underwater shell middens are almost unknown and of uncertain status, and it has generally been assumed that such deposits would not survive the destructive impact of sea-level rise or would be indistinguishable from natural shell deposits. Recently, two examples of underwater shell deposits have been independently discovered and verified as anthropogenic midden deposits – a Mesolithic shell midden on the island of Hjarnø in the Straits of Denmark, and a Middle to Late Archaic shell midden in the Econfina Channel of the Gulf of Mexico, Florida, USA. We report the comparative geoarchaeological analysis of these deposits, using a sedimentological approach to unravel their formation history and post-depositional transformation. Despite the differences in coastal geomorphology and geology, cultural context, molluscan taxonomy and preservation conditions between these sites, the results demonstrate similar sedimentological profiles that are distinctive of anthropogenic deposits, demonstrate their origin as subaerial deposits at the shore edge before inundation by sea-level rise, and show that these properties can be identified in sediment samples recovered from coring. These findings support arguments that such sites likely exist in greater numbers than previously assumed, that they can be identified from minimally invasive techniques without the need for extensive underwater excavation, and that they should be sought to fill critical gaps in the temporal and geographical record concerning Late Quaternary human use of coastal zones and marine resources. Highlights: Shell middens survive submergence by sea-level rise in diverse environments. Shell middens have similar sedimentological profiles regardless of context. Micromorphological analysis demonstrates anthropogenic origin as subaerial deposits. Shell consumption and discard continued during marine transgression. Submerged shell middens can be identified by minimally invasive coring techniques.